The Development of the Atomic Theory of the Formation of a New Phase in Adsorbing Layers in an External Electric Field - Shtapenko, E.Ph.; Tytarenko, V.V.; Zabludovsky, V.A. (Physics and Chemistry of Solid State, 2015)
The article deals with the nucleation rate in the development of the atomic theory. The expression for the calculation of heterogeneous nucleation rate in adsorbed layers in an external electric field, which allows for the stability criterion nucleus of a new phase. For example, the values of nickel electrocrystallisation nucleation rate in the development of the atomic theory and the classical theory of nucleation. A comparison with the experimental values. It is shown that at high overvoltage at the cathode developed atomic theory gives values of the nucleation rate closer to the experimental.